Effects of Onion (Allium cepa L.) Extract on Growth Performance and Carcass Characteristics of Muscovy duck - Keohavong, Bounmy (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This study was designed to evaluate the effect of various levels of onion extract on growth performance and carcass characteristics of Muscovy ducks. Six ducklings were randomly distributed into each replicate pen (total of 12 pens). Four replicate pens for each treatment were randomly selected. Control birds were provided commercial diet. Other two dietary treatments were supplemented with onion extract at the level of 1% and 2%. Body weight, feed intake, body weight gain, and gain:feed of ducklings between control and treatment groups are not differ (p>0.05). The present results showed that onion extract did not affect (p>0.05) overall growth performance of Muscovy ducks during week 4 to week 8 of ages. Percentage of External offals (based on carcass weight) and both carcass weight and carcass yields in this study did not affected (p>0.05) by onion extracts. Abdominal fat of bird receive 2% of onion extract lowest (p<0.05) value compared with control and treatment received 1% of onion extract among the parameters of internal offals. In contrast, the volume of blood of birds received 1% of onion extract shown highest volume (p<0.05). Cooking loss of breast meat between the group of control and onion extract 1% shown not differ (p>0.05). Muscovy ducks received dietary onion extract of 2% shown lowest value of cooking loss (p<0.05). The blood volume and immune organs in this study are shown significant different (p<0.05). In overall, duck received dietary onion extract of 1% shown lowest values of thymus and bursa of fabricius (p<0.05), and also highest volume of blood (p<0.05). The results in this study shown that, different level of dietary onion extracts are influenced on growth performance, carcass characteristics and immune organs of Muscovy ducks from week 4 to week 11 of ages. In conclusion, the present study shown that dietary onion extract of 1% indicated slightly outcome in terms of internal offals improvement and immune organs development. In contrast, this study indicated that dietary onion extract of 2% shown best value of breast meat quality in term of cooking loss. Further research is needed to describe the effects of dietary onion extract on the metabolism and tissue distribution of cholesterol and triacylglycerol in meat-type ducks